The influence of static crack-opening stress on the threshold level for shear-mode fatigue crack growth in bearing steels. (1st April 2017) - Okazaki, S.; Wada, K.; Matsunaga, H.; Endo, M.
Abstract: An investigation was conducted into the influence of statically-applied, mode I, crack-opening load on the threshold condition for propagation of a shear-mode fatigue crack in a bearing steel. Torsional fatigue test was carried out at an R of −1 using a hollow cylindrical specimen into which a semi-elliptical, small slit was axially introduced. A static axial compressive stress was simultaneously applied to suppress crack branching. A coplanar, shear-mode, non-propagating fatigue crack emanating from the slit was attained by appropriate control of shear stress amplitude. Internal pressure was then applied to generate a hoop stress as a static crack-opening stress, σ θ static . Consequently, the threshold shear-mode stress intensity factor range, Δ K τth, was significantly decreased with increase of the static mode I stress intensity factor. To further understand the contribution of σ θ static to the reduction in Δ K τth, microstructural observations for the cross-sections of a non-propagating crack were conducted using a scanning electron microscope in conjunction with the electron backscatter diffraction analysis. The results revealed that the excess loading of σ θ static accounts for the change in the crack-path, resulting in a further reduction in Δ K τth .